Analisis Daya Saing Budidaya Ikan Guppy (Poecilia reticulata) di Kota Jakarta Timur - RIANDI, FAISAL ACHMAD; WIDHIANTHINI, WIDHIANTHINI; SETIAWAN, I GEDE BAGUS DERA (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.11, No.2, Desember 2022DO - 10.24843/JAA.2022.v11.i02.p18, 2022)
Analysis of Business Competitiveness of Guppy Fish Cultivation ( Poecilia reticulata ) in East Jakarta City Indonesian fishery products that are quite popular are ornamental fish. Ornamental fish such as guppy fish are quite popular in Indonesia, especially in the city of East Jakarta. Although guppy fish cultivators in the city of East Jakarta to be able to apply land use in limited land issues, cultivators must continue to apply an efficient system so that still have competitiveness with other regions. The purpose of this study is to identify and analyze comparative and competitive advantages in guppy fish farming based on business scale in East Jakarta City, and to analyze the effect of output prices and input prices on comparative and competitive advantages of guppy fish farming in East Jakarta City. Based on the research results obtained using themethod Policy Analysis Matrix, every large scale business gets a bigger profit compared to the potential scale. Based on the value of Private Cost Ratio and Domestic Resource Cost Ratio which is less than one, it proves that there is competitiveness in the guppy fish farming business in East Jakarta City. The calculation of the value of other indicators analysis shows that the efficiency of the input is not determined by the size of the business scale. In the influence of government policies on input and output, it was found that a decrease in input prices was 17.65% and a combination of decreases in input output could increase the value of comparative and competitive advantage. There is a need for a joint development program that is open to all guppy fish farmers in East Jakarta City, it is necessary to have supporting policies and sustainable research at the national level.